Monetary Policy Transmission Mechanism of Pakistan: Evidence from Bank Lending and Asset Price Channels - Mukhtar, Tayyaba; Younas, Muhammad Zeeshan (Asian Journal of Economic Modelling, 2019)
The lending and asset price transmission channels remain largely unexplored since financial reforms and pursuance of market-based monetary policy instruments. This paper examines the monetary policy transmission mechanisms of Pakistan with a special focus on bank lending and asset price channels. Monthly data over the period 2000M7-2016M12 is being used for the short run analysis. The empirical investigation is based on SVAR framework. The results show that the monetary aggregates targeting agenda is still operative in effecting the output and general price level. Bank lending have a non-trivial part through the investment channel and share prices through wealth effect on price level and output, while the conventional interest rate channel seemed to be ineffective in the transmission mechanism process in Pakistan. The findings of generalized impulse response functions are backed by the generalized error forecast variance decomposition analysis. In addition to domestic variables, external shocks appear to have a strong influence on inflation and output in Pakistan.